"Conspiradores políticos" y "Sectas misteriosas" imaginarios sociales sobre la masonería en Costa Rica (1865-1899) - Martínez Esquivel, Ricardo (2016)
The Masonry found its beginnings due to its secret character and to its participation in different social processes and many politicians with multiple myth inspiration. Many secular reforms in the world during centuries XVIII and XIX were led by affiliates with this association, which is the reason why the stance of the Catholic Church to the masonry was constant. The Catholic Church was taking advantage of its power on the masses to develop a "true ideological battle" . From the ecclesial position, the imagination of the people at the time was representing the masonry that did not have limits. The secret character was based on the idea that was developed that being masonry is bound to the political conspiracy, the religious mystery and or the atheism. Therefore, in the following investigation we analyzed the found documentation and the main present representations in it. The base of this investigation is a speech analysis which was centered in Costa Rica from 1865 to 1899.